Optimisation of Water-Use in Pulp and Paper Mills: A Streamlined Review of Scientific Journal Publications - Ocklind, Felicia; Liback, Kristin; Lundqvist, Lova; Harge, Wilma; Venkatesh, G (Studia Ecologiae et Bioethicae, 2024)
The water-, and energy footprints of the processes in the pulp and paper industry are sizable enough to warrant investment of money and commitment of time truncate the same. Besides, there is also a nexus between water and energy here, with optimisation of the use of one of these resoruces enabling that of the other too. This streamlined review focuses on journal publications (originating from different parts of the world, and targeted at researchers and decision-makers in the industry) which train the lens on the optimisation of water use in this particular sector of the (forestry) bioeconomy. The synergies and complementarities which exist among different sustainable development goals (SDGs) , promise positive ripple effects, caused by attending to the truncation of the water footprint. The articles, in general, recommend effective in-plant wastewater treatment in combinaton with recirculating the treated effluent, and looking upon the water streams as carriers or bearers of valorisable substances – organics which can yield a host of bio-products in bio-refineries, including bio-energy. Availing of water-pinch analysis as a tool to uncover possibilities of water use in a cascade (depending upon the requirements imposed on the water, by processes downstream in the cascade), has been shown to aid in the optimisation of both water use and energy demand within the plant. One case study, for example, showed that the demand for steam can be decreased by about 4 GJ per ton of output, by recovering the waste heat in the water streams.